A statistical quality control study on Unilox Industrial Corporation - Evangelista, Lynn S.; Malaki, Ann Maureen; Reyes, Ma. Criselda; Tobias, Roxanne (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
A quality control Study on Unilox Industrial Corporation, a Philippine-based manufacturing company of industrial chemicals and sacrificial anodes for cathodic protection, was conducted for the purpose of providing feasible recommendations for quality improvement on three of its one-pack stabilizer products, namely EC 201, SME-05 and 1181P. Through observation, personnel interview and analysis, two root problems were identified and consequently addressed in this study. These are the occurrence of non-conformities in one-pack stabilizers, and the use of inappropriate type of mixer. For both problems, appropriate statistical process control tools, specifically Moving Range and Individuals Control Charts, Test for Normality, Process Capability Analysis, and Failure Mode and Effect Analysis (FMEA), were conducted to determine respective suitable solutions. Cost-Benefit Analyses on both the company's original inspection method and the group's feasible recommendations were also performed to compare existing alternatives and come up with the most favorable solutions. Hence, the group proposes the following: (1) equipment inspection at the start of each production, (2) have a standard method for preparation of test specimen, (3) assigning regular operators for a specific machine line, (4) training for the correct processing procedure, (5) use of all digital weighing scales, (6) proceed with incoming surveillance regardless of the presence of COA, and (7) immediately address worker grievances. Implementation of these new schemes will approximately lead to higher efficiency and lesser non-confiming outputs. In addition, the group would like to recommend a study on ergonomic assessment and methods engineering as areas for further study.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Stabilizing agents; Quality control